PEREMPUAN DALAM CERPEN BAHAGIA BERSYARAT KARYA OKKY MADASARI DAN BAU LAUT KARYA RATIH KUMALA [Women in Cerpen Bahagia Bersyarat by Okky Madasari and Bau Laut by Ratih Kumala] - Nurweni Saptawuryandari (TOTOBUANG, 2017)
The rise of women writers in Indonesian literary treasures shows encouraging progress. Okky Madasari and Ratih Kumala as a writer figured how a woman as wife accepts her destiny and nature in living her household life. The household that nodded by both female characters were expressed by Okky Madasari through her short story entitled "Bahagia Bersyarat" and Ratih Kumala through her short story entitled "Bau Laut". Both female characters were depicted very sincere, patient and accept what the will of her husband. The movement and behavior to rebel from the life that befell her was not done by the two female characters. Whether the two figures portrayed by these two female authors are embodiments of the lives of the two authors or only imaginary images, sociological analysis is necessary. For that, through this paper will be disclosed whether there is a sociological linkage between the work he wrote with the life of the author.Maraknya penulis perempuan dalam khasanah sastra Indonesia menunjukkan perkembangan yang menggembirakan. Okky Madasari dan Ratih Kumala sebagai seorang penulis mengejawantahkan  bagaimana perempuan sebagai seorang  istri menerima takdir dan kodratnya dalam menjalani kehidupan rumah tangganya. Biduk rumah tangga yang dijalani kedua tokoh perempuan diungkapkan  oleh Okky Madasari melalui cerpennya yang berjudul “Bahagia Bersyarat” dan Ratih Kumala melalui cerpennya yang berjudul “Bau Laut”. Kedua tokoh perempuan digambarkan sangat ikhlas, sabar dan menerima apa kehendak dari suaminya. Gerak dan perilaku untuk memberontak dari kehidupan yang menimpanya tidak dilakukan oleh kedua tokoh perempuan itu. Apakah kedua tokoh yang digambarkan oleh kedua penulis perempuan ini merupakan pengejawantahan dari kehidupan kedua penulis itu atau hanya gambaran imajiner saja, perlu analisis secara sosiologis. Untuk itu, melalui tulisan ini akan diungkapkan apakah ada keterkaitan secara sosiologis antara karya yang ditulisnya dengan kehidupan penulisnya.